APPLICATION OF ORGANIZATIONAL CULTURE AT THE SIDOARJO TAX SERVICE OFFICE - Aufa Anggarda, Achmad; Prastyawan , Agus; Isbandono, Prasetyo (Transpublika Publisher, 2021)
Organizational culture can be applied and becomes strong if every individual involved in an organization participates in supporting the goals contained in the organization. Organizational culture has an important role in the organization. The purpose of this study is to describe the application of organizational culture in the Sidoarjo District Tax Office. The research approach is qualitative research. Data collection techniques using interviews, observation and documentation. And data analysis techniques are data collection, data reduction, data presentation and verification or drawing conclusions so that the data collected is good enough to be used as material for scientific work. The results of the study describe the application of organizational culture in the Sidoarjo Middle Tax Office to apply levels, namely artifacts and creations, values ​​and basic assumptions. In the application of various artifacts and creations such as logos, building architecture, layout, uniforms, organizational structures, working hours and banners. The values ​​applied are the vision and mission, the values ​​of the Ministry of Finance, the Code of Ethics, and the DGT Cultural Program. Organizational culture constraints which consist of problems of external adaptation of organizational culture and problems of internal integration of organizational culture. Suggestions related to the application of organizational culture in the obstacles faced are employees must always improve performance optimization so that in achieving tax revenue that can exceed targets and are not burdened by other employees, then employees must also improve discipline and all employees can use Indonesian because the language expected in the Sidoarjo Middle Tax Office can facilitate the understanding of all employees with the Indonesian language group, namely Indonesian.